Implementasi Sistem Pakar Berbasis Web Untuk Diagnosis Penyakit Tanaman Padi Menggunakan Metode Naive Bayes Di Balai Penyuluh Pertanian Kecematan Moyo Hulu - Susanto, Eri Sasmita; Aldy, Aldy; Esabella, Shinta; Ekastini, Ekastini; Aldy (Universitas Komputer Indonesia, 2026)
This study developed a web-based expert system for diagnosing rice plant diseases using the Naive Bayes Classifier method and the Spiral Model software development model. The Spiral approach allows for iterative development with a focus on risk management and validation by agricultural experts. The system includes 12 disease types and 27 symptoms, and generates probabilistic diagnoses along with recommended actions. Testing on 21 cases demonstrated 95.24% accuracy compared to expert assessment, demonstrating the effectiveness of this method in providing a reliable diagnostic tool to support national food security.